2019
DOI: 10.1159/000495282
|View full text |Cite
|
Sign up to set email alerts
|

Guidelines for Colonic Diverticular Bleeding and Colonic Diverticulitis: Japan Gastroenterological Association

Abstract: Colonic diverticular disease has been increasing in prevalence in Japan due to the rapidly aging population. Colonic diverticular bleeding can result in hemorrhagic shock requiring blood transfusion, and it carries a high risk of recurrence within 1 year. Colonic diverticulitis can cause abscess, fistula formation, and perforation of the colon that may require surgery, and it often recurs. As a result, patients with colonic diverticular disease are often bothered by required frequent examinations, re-hospitali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
168
2
19

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 149 publications
(215 citation statements)
references
References 177 publications
(284 reference statements)
6
168
2
19
Order By: Relevance
“…In Japan, the rising prevalence of both colonic diverticula and CDB has increased the associated clinical burden including medical costs. Accordingly, growing concern about the management of colonic diverticular disease promoted the development of practice guidelines, particularly given the East‐West paradox in disease prevalence, phenotype, and medical burden . The guidelines indicated a clinical flow chart (Fig.…”
Section: Recent Advances In the Management Of Cdb: Ligation Therapy Hmentioning
confidence: 99%
See 1 more Smart Citation
“…In Japan, the rising prevalence of both colonic diverticula and CDB has increased the associated clinical burden including medical costs. Accordingly, growing concern about the management of colonic diverticular disease promoted the development of practice guidelines, particularly given the East‐West paradox in disease prevalence, phenotype, and medical burden . The guidelines indicated a clinical flow chart (Fig.…”
Section: Recent Advances In the Management Of Cdb: Ligation Therapy Hmentioning
confidence: 99%
“…Accordingly, growing concern about the management of colonic diverticular disease promoted the development of practice guidelines, particularly given the East-West paradox in disease prevalence, phenotype, and medical burden. 20 The guidelines indicated a clinical flow chart ( Fig. 1) and practical recommendations for the diagnosis and treatment of patients with CDB.…”
Section: Recent Advances In the Management Of Cdb: Ligation Therapy Hmentioning
confidence: 99%
“…In Japan, colonic diverticular hemorrhage is increasingly common with aging population and westernization of dietary habits, and valuable treatment options should be fully discussed for the management of colonic diverticular hemorrhage. Currently, Japanese guidelines proposed early colonoscopy as the triage tool for patients with sustained bleeding although it remains controversial whether early colonoscopy would contribute to increase in identification of SRH or prevention of rebleeding [6]. On the contrary, our results in a real clinical setting suggested that colonic diverticular hemorrhage would stop spontaneously without any interventions, i.e., with only conservative treatment, except for the cases with shock based on vital signs and extravasation on CECT.…”
Section: Discussionmentioning
confidence: 62%
“…In Japanese guidelines for colonic diverticular hemorrhage, it is proposed that early colonoscopy would be preferably performed within 24 hours of hospital visit to identify the stigma of recent hemorrhage (SRH) [6], and several institutions have actively performed early colonoscopy. In addition, some new endoscopic techniques, which might contribute to increase in successful hemostasis and decrease in rebleeding, have been recently reported, such as endoscopic band ligation, endoscopic detachable snare ligation, and over-the-scope clip (OTSC ® , Ovesco Endoscopy, Tübingen, Germany) [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Again, colonic diverticular bleeding is shown to be significantly more common in males and elderly patients aged ≥60 years [12], and NSAID and LDA have been reported as risk factors [13]. Our patient had a history of LDA use and was ineligible for endoscopic hemostasis and underwent colectomy according to the current guidelines [14].…”
Section: Discussion/conclusionmentioning
confidence: 90%